2008
DOI: 10.1016/j.ijsolstr.2007.09.025
|View full text |Cite
|
Sign up to set email alerts
|

A micromechanical model of elastoplastic and damage behavior of a cohesive geomaterial

Abstract: The present study is devoted to the development and validation of a nonlinear homogenization approach of the mechanical behavior of Callovo-Oxfordian argillites. The material is modeled as an heterogeneous composite composed of an elastoplastic clay matrix and of linear elastic or elastic damage inclusions. The macroscopic constitutive law is obtained by adapting the incremental method proposed by Hill [Hill, R., 1965. Continuum micro-mechanics of elastoplastic polycrystals. J. Mech. Phys. Solids 13, 89-101]. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…A number of experimental studies showed different modes of initiation and propagation of microcracks in rock material. Two important basic micromechanical models in damage mechanics were proposed to account for the correlation between the deformation and failure of rock and the growth of microcracks (Guéry, Cormery, Shao, & Kondo, 2008;Kondo, Welemane, & Cormery, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A number of experimental studies showed different modes of initiation and propagation of microcracks in rock material. Two important basic micromechanical models in damage mechanics were proposed to account for the correlation between the deformation and failure of rock and the growth of microcracks (Guéry, Cormery, Shao, & Kondo, 2008;Kondo, Welemane, & Cormery, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The homogenized mechanical behavior of RVE can be expressed by linear relationships between the stress and the strain at the macroscopic scale. In the case of the homogeneous strain imposed on the RVE boundary, using the relations (6), (8) and the behavior law (1), this behavior is written in the form:…”
Section: Homogenizationmentioning
confidence: 99%
“…On the other hand, the specimens used in macro-scale laboratory creep tests needed to meet strict size requirements: the typical cylindrical specimen size was Φ50 mm×100 mm (Mishra and Verrna, 2015) and the size of the smaller prismatic samples was 25 mm×25 mm×50 mm (Lu and Wang, 2017). Besides, centimetre-scale laboratory experiments regard rocks consisting of various constituents (Guery et al, 2008) as homogeneous bodies, where the underlying mechanism of large creep deformation of soft mudstone yet remains to be relatively insufficiently understood. Adopting a new technique to identify various mineralogical constituents and investigate their creep characteristics is very meaningful since the individual behaviour of each constituent dictates the overall behaviour of macro-scale mudstone.…”
Section: Introductionmentioning
confidence: 99%